PELATIHAN PENGEMBANGAN MEDIA INFORMASI BERBASIS CANVA UNTUK MENINGKATKAN KREATIVITAS REMAJA KARANG TARUNA DALAM MENINGKATKAN EKONOMI KREATIF DESA TROPODO KRIAN SIDOARJO - Budi Purwantiningsih; Nayla Najma Arifin; Novita Andriana; Ainur Rosyidah; Elok Imroatul Azizah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Information media is widely used in daily activities, including social media, marketplaces, promotions, banners, flyers, pamphlets, and brochures. However, to effectively engage the community, the chosen media must feature well-designed, unique, and attractive visuals that motivate action. Tropodo Village has an official website but lacks the human resources to utilize it for promoting local products through the development of Micro, Small, and Medium Enterprises (MSMEs) and the "Bumi Asih" Village-Owned Enterprise (Bumdes). To address this issue, this empowerment program employed the Asset-Based Community Development (ABCD) method. The results demonstrated success in creating copywriting and Canva-based content, with 80% of participants gaining an understanding of how to design appealing content that attracts consumers. This initiative has contributed to enhancing the creative economy within the Tropodo Village community.